Developing Healthcare Complaints Analysis Tool for Health System: A Cross‐Sectional Study - Ali Vafaee Najar; Damoon Gorji; Hoorang Nazari Ardabili; Maryam Pourshirazi; Elaheh Houshmand (Health Science Reports)
ABSTRACT Background and Aims The role of the healthcare system in the provision, maintenance, and promotion of public health is associated with handling healthcare complaints. This notion as the principle of accountability requires the authorities' attention. This study aimed to develop the Healthcare Complaints Analysis Tool (HCAT) in Iran. Methods Following a comprehensive review of the country and field studies conducted in the Medical System Organization and Universities of Medical Sciences, the features of patients' complaints were extracted from medical centers and hospitals. Then, experts who were experienced in health and medical areas localized HCAT through translation and re‐translation process using the Delphi technique. Finally, the healthcare complaints were classified according to the localized HCAT components. Result Using HCAT showed that in Iran's healthcare system, complaints were related to relative frequency and percentage of all types of complaints. However, there is a lack of a mechanized registration system, investigation, analysis, and classification of healthcare complaints. Conclusions Providing medical centers with such a system by the ministry of health and mandatory reporting of complaints may lead to coding complaints, measure the severity of complaints, service monitoring and organizational learning.